Revisiting the relationship between attitudes and retirement planning behavior: a study on personal financial planning - Rosle Mohidin; Amer Azlan Abdul Jamal; Caroline Geetha Arokiadasan; Lim, Thien Sang; Mohd Rahimie Abdul Karim (2013)
Retirement planning becomes a crucial concern as the life expectancy has increased as well as the rises of health care costs. This study attempts to investigate the relationship between attitudes towards personal financial planning with retirement planning behavior among workers in Kota Kinabalu who have opted for EPF as their retirement benefit. The moderating effects of age and income on aforesaid the five dimension attitudes of personal financial planning has also been investigated. A total of 200 respondents were used and the results revealed that retirement planning behavior can be explained by 10.9 percents of five dimensions of attitudes towards personal financial planning. Retirement planning, money management, investment planning, and estate planning were found to have significant positive relationship with retirement planning behavior. However, the moderator factor of age only has significant influence on the estate planning. The implication was useful for the financial planners and government to do the adjustment and propose more optional solution regarding retirement issues.